Hypermethioninemia due to methionine adenosyltransferase I/III deficiency and brain damage - Xue Ma; Mei Lu; Zhehui Chen; Huiting Zhang; Jinqing Song; Hui Dong; Ying Jin; Mengqiu Li; Ruxuan He; Lulu Kang; Yi Liu; Yongxing Chen; et al. (BMC, 2024)
Abstract Background and objectives Methionine adenosyltransferase I/III deficiency used to be considered a relatively benign disease. This study aims to elucidate the clinical characteristics of methionine adenosyltransferase I/III deficiency patients with neurological manifestations. Methods The clinical data, blood amino acids, plasma total homocysteine, gene variants, brain imaging, treatments and outcomes of 15 patients with methionine adenosyltransferase I/III deficiency were retrospectively analyzed. Results Of these 15 patients, 10 demonstrated neurological abnormalities, with delayed language development, learning difficulties or abnormal brain imaging findings. Eleven patients were identified by newborn screening. Patients with demyelination showed significantly higher blood methionine concentrations at baseline (1102 vs. 396 µmol/L), and their blood methionine remained markedly elevated despite a low-methionine diet. Their plasma total homocysteine was normal to moderate elevated. One patient underwent liver transplantation aged 8 years, which reduced his serum methionine concentration to normal. Compound heterozygous and homozygous MAT1A variants were identified from the patients. Among the 21 variants observed, nine have been reported previously, while 12 were novel. Conclusions Methionine adenosyltransferase I/III deficiency is not just a benign disease. Severe persistent hypermethioninemia can cause brain injuries, especially in the white matter. Liver transplantation may be a potential treatment option for refractory methionine adenosyltransferase I/III deficiency.